2005
DOI: 10.1148/radiol.2362040739
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer: Correlation of MR Imaging and MR Spectroscopy with Pathologic Findings after Radiation Therapy–Initial Experience

Abstract: PURPOSE:To prospectively evaluate magnetic resonance (MR) imaging and MR spectroscopy for depiction of local prostate cancer recurrence after external-beam radiation therapy, with stepsection pathologic findings as the standard of reference. MATERIALS AND METHODS:Study received institutional approval, and written informed consent was obtained. Study was compliant with Health Insurance Portability and Accountability Act. Sextant biopsy, digital rectal examination, MR imaging, MR spectroscopy, and salvage radica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
113
1
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(121 citation statements)
references
References 51 publications
3
113
1
4
Order By: Relevance
“…After RT, however, the ratio Cho+Cr/Ci is of limited use due to citrate and choline signals that are often undetectable. MRI studies before salvage prostatectomy have shown sensitivity and specificity rates of 36-76% and 65-81%, respectively [14,16]; thus in good agreement with our findings (i.e., equivocal or false positive images in 75% of cases).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…After RT, however, the ratio Cho+Cr/Ci is of limited use due to citrate and choline signals that are often undetectable. MRI studies before salvage prostatectomy have shown sensitivity and specificity rates of 36-76% and 65-81%, respectively [14,16]; thus in good agreement with our findings (i.e., equivocal or false positive images in 75% of cases).…”
Section: Discussionsupporting
confidence: 92%
“…The value of MRS in recurrent prostate cancer after RT is controversial [14,15]. Spectroscopy usually detects prostate cancer based on the ratio between a high choline + creatinine signal (tumor) and a reduced citrate signal (normal tissue).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of the proposed system has to be explored further with respect to different features that can be extracted from both of the aforementioned imaging modalities. Equally important, information from other MRI techniques, such as T2 ADC mapping methods [26] and magnetic resonance spectroscopy [27] might increase the separation ability between malignant and benign tissue even more. Moreover, the performance of other pattern recognition schemes such as the Support Vector Machines [28] has to be evaluated so as to determine a good combination of features and classifier for the problem at hand.…”
Section: Resultsmentioning
confidence: 99%
“…Because an irradiated prostate gland usually appears small and diffusely hypointense in T2-weighted images, MRS, which detects abnormal metabolism rather than abnormal anatomy, has been shown to be a better technique for the detection of local tumor recurrence and complete metabolic atrophy (1). In addition, MRS allows tumors to be distinguished from normal glandular tissue on the basis of an increased choline plus creatine to citrate ratio (19). In studies analyzing the correlation between whole-mount histopathology and MRS, the sensitivity and specificity of MRS range between 29-89% and 62-95%, respectively (20); however, the sensitivity of MRS depends on the Gleason score.…”
Section: Discussionmentioning
confidence: 99%